Zero-Tension Lysimeter for use in greywater irrigation monitoring - Radin Mohamed, Radin Maya Saphira (International Journal of Integrated Engineering, 2012)
The main purpose of the study was to develop a new zero-tension lysimeter (ZTL) as a leachate sampler in a greywater irrigation plot. Greywater is known as a wastewater that is generated from baths, showers, washing machines, laundry troughs, dishwashers and kitchen sinks; but excludes toilet wastes. The use of greywater is becoming increasingly acceptable to supply non-potable irrigation needs. However, some questions have been raised about the pollution risk of soil and receiving waters due to the content of different pollutants from the household washing activities. In this study, the new ZTLNs were trialled to compare the quantity and quality of leachate collected with the conventional pan lysimeter (ZTLP) in the pilot scale study. The calculated leachate volume incorporated a water balance using the Penman-Monteigh model. The results indicate that the new lysimeter designated as ZTL (N1), produced the lowest mean percentage deviation from the calculated volume (CV), 3.90 %. ZTL (N1) was also cost effective and required limited effort to install using an auger, which also minimises soil disturbance.to install at household sites. Consequently, the lysimeter was established to facilitate the monitoring of greywater irrigation.